Ventricular assist device implantation improves skeletal muscle function, oxidative capacity, and growth hormone/insulin‐like growth factor‐1 axis signaling in patients with advanced heart failure. Issue 4 (7th August 2014) - Khawaja, Tuba; Chokshi, Aalap; Ji, Ruiping; Kato, Tomoko S.; Xu, Katherine; Zizola, Cynthia; Wu, Christina; Forman, Daniel E.; Ota, Takeyoshi; Kennel, Peter; Takayama, Hiroo; Naka, Yoshifumi; et al.
Abstract : Background: Skeletal muscle dysfunction in patients with heart failure (HF) has been linked to impaired growth hormone (GH)/insulin‐like growth factor (IGF)‐1 signaling. We hypothesized that ventricular assist device (VAD) implantation reverses GH/IGF‐1 axis dysfunction and improves muscle metabolism in HF. Methods: Blood and rectus abdominis muscle samples were collected during VAD implantation and explantation from patients with HF and controls. Clinical data were obtained from medical records, biomarkers measured by enzyme‐linked immunosorbent assay (ELISA), and gene expression analyzed by reverse transcription and real‐time polymerase chain reaction (RT‐PCR). Grip strength was assessed by dynamometry. Oxidative capacity was measured using oleate oxidation rates. Muscle fiber type and size were assessed by histology. Results: Elevated GH (0.27 ± 0.27 versus 3.6 ± 7.7 ng/ml in HF; p = 0.0002) and lower IGF‐1 and insulin‐like growth factor binding protein (IGFBP)‐3 were found in HF (IGF‐1, 144 ± 41 versus 74 ± 45 ng/ml in HF, p < 0.05; and IGFBP‐3, 3, 880 ± 934 versus 1, 935 ± 862 ng/ml in HF, p = 0.05). The GH/IGF‐1 ratio, a marker of GH resistance, was elevated in HF (0.002 ± 0.002 versus 0.048 ± 0.1 pre‐VAD; p < 0.0039). After VAD support, skeletal muscle expression of IGF‐1 and IGFBP‐3 increased (10‐fold and 5‐fold, respectively; p < 0.05) accompanied by enhanced oxidative gene expression (CD36, CPT1, and PGC1α) and increased oxidation rates (+1.37‐fold; p < 0.05). Further, VAD implantation increased the oxidative muscle fiber proportion (38 versus 54 %, p = 0.031), fiber cross‐sectional area (CSA) (1, 005 ± 668 versus 1, 240 ± 670 μm 2, p < 0.001), and Akt phosphorylation state in skeletal muscle. Finally, hand grip strength increased 26.5 ± 27.5 % at 180 days on‐VAD ( p < 0.05 versus baseline). Conclusion: Our data demonstrate that VAD implantation corrects GH/IGF‐1 signaling, improves muscle structure and function, and enhances oxidative muscle metabolism in patients with advanced HF.